Applying the SCRUM Framework in Managing the Development of Candidate Profiling Project (A Case Study of Bagidata) - Trian Afiansyah; Achmad Sidik; Zainul Hakim; Detin Sofia (JURNAL SISFOTEK GLOBAL, 2023)
Bagidata is a people analytics platform that provides various data analysis solutions for Human Resource Management. Bagidata develops and maintains an application for creating candidate profiles using SCRUM and Agile. However, there are still many obstacles in the SCRUM and Agile processes in developing this application, such as all documentation being done manually with Microsoft Excel and separated, the inability to monitor the process, the and lack of an integrated platform for team members to share work and make documentation. Therefore, a system is needed to facilitate application development and become an integrated platform for application work, monitoring, and web-based documentation. This study uses object-oriented methodology or OOAD (Object Oriented Analysis and Design), and the data collection method is through observation, interviews, and literature review. This web-based application uses Javascript programming language, PostgreSQL database, and Visual Studio Code as tools, as well as UML modeling with 4 design diagrams, namely a use case diagram, activity diagram, sequence diagram, and class diagram. The results of this study are expected to enable the product owner and development team to monitor the development process, organize task allocation among team developers, and provide an integrated platform for documentation, thus improving the candidate profiling application development process.